Linking energy policy, energy insecurity, and health outcomes - Tang, Tian; Kim, Hyunji (Frontiers in Sustainable Energy Policy, 2023)
Energy insecurity poses a global challenge with far-reaching social equity and health implications. This paper provides a comprehensive perspective on the relationship between energy insecurity and health outcomes in developed countries. Existing research has identified associations between energy insecurity and various physical and mental health outcomes. Moreover, climate change can exacerbate the adverse health consequences of energy insecurity, disproportionately affecting vulnerable populations. Based on a review of existing literature, this paper identifies several knowledge gaps, proposes future research directions, and discusses data challenges faced by researchers in measuring energy insecurity and assessing the health impacts of existing programs that tackle energy insecurity. Furthermore, the paper highlights the importance of fostering collaboration among different governmental agencies and other sectors to enhance energy insecurity program management and data collection for program evaluation.